The Buffalo Genome and the Application of Genomics in Animal Management and Improvement - Iamartino, Daniela; Williams, John L.; Sonstegard, Tad; Reecy, James; Van Tassell, Curtis; Nicolazzi, Ezequiel L.; Biffani, Stefano; Biscarini, Filippo; Schroeder, Steven; Oliveira, Denise A. A. de; Coletta, Angelo; Garcia, José Fernando [UNESP]; et al. (Int Buffalo Information Ctr, 2013)
The publication of the human genome sequence in 2001 was a major step forward in knowledge necessary to understand the variations between individuals. For farmed species, genomic sequence information will facilitate the selection of animals optimised to live, and be productive, in particular environments. The availability of cattle genome sequence has allowed the breeding industry to take the first steps towards predicting phenotypes from genotypes by estimating a genomic breeding value (gEBV) for bulls using genome-wide DNA markers. The sequencing of the buffalo genome and creation of a panel of DNA markers has created the opportunity to apply molecular selection approaches for this species.The genomes of several buffalo of different breeds were sequenced and aligned with the bovine genome, which facilitated the identification of millions of sequence variants in the buffalo genomes. Based on frequencies of variants within and among buffalo breeds, and their distribution across the genome compared with the bovine genome, 90,000 putative single nucleotide polymorphisms (SNP) were selected to create an Axiom (R) Buffalo Genotyping Array 90K. This SNP Chip was tested in buffalo populations from Italy and Brazil and found to have at least 75% high quality and polymorphic markers in these populations. The 90K SNP chip was then used to investigate the structure of buffalo populations, and to localise the variations having a major effect on milk production.
Keywords: genetic association study; genomic selection; genome sequence; single nucleotide polymorphisms